(untitled) (PlaySpace, 2023)
In this essay I analyze how the artifacts of questioning and listening became resourceful in the procedure of excavating the personal and political reasons behind the migration journey my maternal grandmother Voinha (who turned 100 years old on April 08th 2021 and passed away on March 06th 2022) embarked on in 1945 from Ananindeua and Belém (Amazon rainforest region) to Rio de Janeiro (BR); and further, my own immigration journey from Latin America to the Middle East and on to northern Europe, fifteen years ago. How coupling questioning with listening allowed an oppressed woman to speak for herself, fostering in this way dramaturgies that brought awareness to feminist empowerment as a means to tackle the colonial and patriarchal ways in which the Brazilian national identity, among many others, is constructed. The writing style is mainly anecdotal and based on conversations I had with Voinha on different occasions. The recordings of our last in-person encounter on September 15th 2018 became the foundation for the performance Feliz Aniversário, created primarily as a way of giving Voinha agency in telling her own migration journey. Excerpts of this audio and video footage will be further analyzed alongside this essay. The methodology adopted is autoethnography with the intention to offer nuanced, complex, and specific knowledge about particular lives, experiences and relationships (Adams, Jones, Ellis 2014). Within autoethnographical methodological tools, I delve on reflexivity with the aim of troubling the relationship between researchers ‘selves’ and ‘others’ and offering a re-examination of the paradigm modernity/coloniality as simultaneously shaped through specific articulations of race, gender and sexuality (Lugones 2007). The final intention is to analyze how turning back to my ancestors’ and my own experiences, identities, and their socio-political implications; how analyzing them according to gender and queer theories and from a decolonial perspective, could potentialize my current practice focused on autobiographical performance. One last important point to be acknowledged is my role as an artist-researcher examining the complex ethical and creative processes of working with intimate family memories, observing the growing necessity of developing dramaturgies of care and resistance (Malzacher 2008).